2020
DOI: 10.3389/fimmu.2020.00944
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease (COVID-19–SARS-CoV-2) and Nutrition: Is Infection in Italy Suggesting a Connection?

Abstract: Novel coronavirus disease (COVID-19) was declared a global pandemic on March 11, 2020. The outbreak first occurred in Wuhan, Hubei, China, in December 2019 and hit Italy heavily in February 2020. Several countries are adopting complete or partial lockdown to contain the growth of COVID-19 infection. These measures may affect people's mental health and well-being but are necessary to avoid spreading the pandemic. There has been a gradual increase in studies exploring prevention and control measures, and we reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 58 publications
3
49
0
Order By: Relevance
“…Diabetes is the most common comorbidity observed in infected deceased patients in Italy, after hypertension ( 30 ). Furthermore, recent data showed a high prevalence of obesity (26%) and overweight (41%) in 928 Italian patients, median age 65 years, from 76 different Italian ICUs, confirming evidence available so far in the literature supporting impaired immune response to viral infections ( 31 ). Therefore, beyond the infectious capacity of this virus, it is important to focus on those elements of modern society which could increase citizens' vulnerability, including diet, lifestyle and environmental factors, strictly linked to morbidity and mortality for all Non-Communicable Diseases (NCDs) ( 32 , 33 ).…”
Section: Citizen Fortificationsupporting
confidence: 79%
“…Diabetes is the most common comorbidity observed in infected deceased patients in Italy, after hypertension ( 30 ). Furthermore, recent data showed a high prevalence of obesity (26%) and overweight (41%) in 928 Italian patients, median age 65 years, from 76 different Italian ICUs, confirming evidence available so far in the literature supporting impaired immune response to viral infections ( 31 ). Therefore, beyond the infectious capacity of this virus, it is important to focus on those elements of modern society which could increase citizens' vulnerability, including diet, lifestyle and environmental factors, strictly linked to morbidity and mortality for all Non-Communicable Diseases (NCDs) ( 32 , 33 ).…”
Section: Citizen Fortificationsupporting
confidence: 79%
“…This deteriorated nutritional status seems to be involved in the virulence of the virus, and probably in the clinical outcome. In this regard, studies conducted in Italy have demonstrated the importance of maintaining/recovering an adequate nutritional status in the clinical outcomes of the patients [89,90].…”
Section: Protein-energy Malnutritionmentioning
confidence: 99%
“…The nutritional status of the human body plays a pivotal role in developing an effective and appropriately balanced immune response to pathogenic viruses (9). Recent studies confirmed the importance of host nutritional status in surviving the COVID-19 challenge (6,10,11). The protein-energy malnutrition (PEM) causes an imbalanced immune response to viral pathogens that can result in infiltration of the lungs by inflammatory cells and the development of pneumonitis following viral infection (12).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the vitamins (A, pyridoxine, cobalamin, folate, C, D, and E) and trace minerals such as Zn, Cu, Se, and Fe takes the crucial role to maintain and support the immune system (6). Balanced nutrition and intake of nutrients in appropriate amounts and composition may reduce the levels of pro-inflammatory cytokines and their side effects in COVID-19 patients (10).…”
Section: Introductionmentioning
confidence: 99%